Analisis Kemampuan Literasi Digital Siswa Dalam Pembelajaran Hybrid di Sekolah Menengah Kejuruan - SAS, Abdillah; Andi Muh Akbar Saputra; Farman, Indra (Jurnal Pekommas, 2023)
The COVID-19 pandemic has shifted all learning patterns from offline to online to hybrid, in which hybrid learning pattern is a combination of offline learning and online learning. The hybrid learning process is closely related to digital literacy skills, therefore research is needed to determine the digital literacy level of vocational high school students when studying online or offline. The digital competency tested in this research is the Digital Literacy Competency of the Ministry of Communications and Informatics, SiBerkreasi & Deloitte (2020) where digital literacy competency is divided into 4 competencies, namely digital skills, digital culture, digital ethics, and digital safety. The summary of research results collected from 108 students through a questionnaire with 30 indicators to measure all students' digital literacy abilities is that empirical descriptive data shows students with digital literacy skills in the low category of 18.5%, the medium category of 65.7% and the high category of 15.7%, which can be concluded that that on average students have moderate literacy skills which are shown at 65.7%. This is of course good, but must still be improved.